Beamsteering antennas using liquid crystals for 5G applications - Divya Krishnan (Nanyang Technological University, 2020)
The existing methods of beamscanning technologies and the drawbacks of each as well as need for a more easy-to-integrate beamscanning techniques, the properties of Liquid Crystals that make it suitable for it and Liquid Crystal based novel beamscanning methods for 5G communication are covered.